PERANANPENDIDIKAN KEWARGANEGARAAN SEBAGAI PILAR PENDIDIKAN HAK ASASI MANUSIA - Nadziroh Nadziroh (Universitas Sarjanawiyata Tamansiswa, 2016)
Human Rights are a foundamental problem in every country, especially in the developing country such as Indonesia. Eventhough, the state had given protection of human right for every body, but in Indonesia there a many breakdowns of it. As a democratic state, Indonesia has to regard human right. It is beause the human rights were the core of democratic principle. So, the human rights must be trained in the school for every student. By using this way, every body can know what their rights and obligations verywell. Civis eduation can be a vehicle for this goal, because it’s one of lessons that talk about human rights and be learned in all school.